Respuesta :
Answer with Explanation:
We are given that
Mass of rock=m
Maximum height=h
a.At maximum height, velocity,v=0
We know that
[tex]v^2=u^2-2gh[/tex]
[tex]0+2gh=u^2[/tex]
[tex]u^2=2gh[/tex]
Height,h=h/4
Again,[tex]v'^2=u^2-2g\times \frac{h}{4}[/tex]
[tex]v'^2=2gh-\frac{gh}{2}=\frac{4gh-gh}{2}=\frac{3gh}{2}[/tex]
[tex]v'=\sqrt{\frac{3gh}{2}}=\sqrt{\frac{3\times 9.8 h}{2}}=3.83\sqrt h[/tex]
Where [tex]g=9.8 m/s^2[/tex]
b.When height,h=3h/4
[tex]v'^2=u^2-2gh[/tex]
[tex]v'^2=2gh-2g\times \frac{3h}{4}=2gh-\frac{3gh}{2}=\frac{4gh-3gh}{2}=\frac{gh}{2}[/tex]
[tex]v'=\sqrt{\frac{9.8h}{2}}=2.2\sqrt h[/tex]
[tex]v'=2.2\sqrt h[/tex]
Answer:
Explanation:
mass of rock = m
height reached = h
let the rock is thrown with velocity u .
At maximum height the velocity of rock is zero.
By using third equation of motion
v² = u² - 2gh
0 = u² - 2 gh
h = u² / 2g .... (1)
(a)
Let the velocity is v at height h/4.
Again using third equation of motion
v² = u² - 2g h/4
v² = u² - 2 g x u²/8 g = 3u²/4
v = 0.866 u
Substitute the value of u from equation (1)
v = 0.866 x √2gh = 3.84 √h
(b) Let v be the velocity at height 3h/4
Again using third equation of motion
v² = u² - 2gx 3h/4
v² = u² - 6 g x u²/8 g = u²/4
v = 0.5 u
Substitute the value of u from equation (1)
v = 0.5 x √2gh = 2.2 √h